DYNAMICS OF THE NUMBER OF RED BLOOD CELLS IN THE BLOOD OF PIGS OF DIFFERENT TYPES OF HIGHER NERVOUS ACTIVITY UNDER THE INFLUENCE OF “JODIS-CONCENTRATE” - Карповський, В. І.; Максін, В. І.; Трокоз, В. О.; Криворучко, Д. І.; Трокоз, А. В.; Шестеринська, В. В. (Scientific Progress & Innovations, 2013)
Based on the research, the results of which are described in the article, the use of raw material for the production of iodine products “Jodis-concentrate” as an effective prophylactic and treatment drug in growing pigs is recommended. This makes it possible to increase the number of red blood cells in the blood of animals that improves indicators of the reactivity of their organism. Use of the drug “Jodis-concentrate” in a dose of 0.12 mg per 1 kg of body weight, 2 times a day for 40 days to the pigs increases the number of red blood cells, especially in animals of severe types of higher nervous activity, which increases the resistance of the organism.